You Are Not Alone. Supporting Health Professionals Following a Clinical Error. Understanding the Psychological Impact That Clinical Error Has on Health Professionals and if Organisational Culture Influences the Experience of the Health Professional - Moore, Emma (Auckland University of Technology, 2025)
Background: Despite significant advancements in patient safety over the past two decades, everyday patients continue to be harmed. In the context of the escalating pressures of increasing workloads, staff shortages, burnout, low morale and high staff turnover faced by healthcare organisations, the negative impact these pressures have on patient care is evident. Well-trained staff with years of experience can make errors. These individuals who make an error are recognised as the ‘second victims’ (Wu, 2000). Becoming a second victim can have severe negative effects that are often long-lasting on a health professional’s psychological and physical well-being, and in turn can negatively impact patient care. Organisational support and a positive safety culture play a critical role in lessening the effects of the second victim phenomenon. This research offers a unique insight into the current situation within New Zealand and contributes to the international literature relating to clinical error and the second victim phenomenon. The aims of this research were, to answer the following questions: I. What psychological impact does involvement with clinical error have on New Zealand health professionals? II. What impact does organisational culture have on the recovery of health professionals following a clinical error? III. What support do health professionals want following a clinical error? Method: This research adopted a mixed-method embedded convergent parallel design; the study was largely quantitative and included qualitative data to enhance the quantitative results. The quantitative data was collected using a self-reporting survey tool with a Likert scale. The tool was developed by combining selected questions taken from three existing tools, The Second Victim Experience and Support Tool, The Safety Attitudes Questionnaire and The Safety Climate Survey, with the inclusion of two open ended questions. The study included a final sample of 41 participants, all registered New-Zealand-based health professionals, including doctors, nurses, medical imaging technologists and clinical pharmacists. Findings: There were several significant findings, many of which were consistent with other published studies. Overall, participants experienced greater psychological distress than physical distress. The most reported psychological symptom was the ‘fear of embarrassment.’ Female participants experienced more severe psychological and physical effects (p=0.045) than males, whilst medical imaging technologists reported more severe psychological effects than nurses or doctors. The most desired support following involvement with a clinical error was colleague support. The difference between gender was statistically significant (p=0.002), and females reported a stronger desire for support than males (p=0.037). Conclusion: This research has identified that the second victim phenomenon is real and is not well managed. There are several nuances that this study has observed across the different professional groups. These major findings provide a unique insight into the experience of New Zealand health professionals and has contributed to the existing second victim and safety culture research, including a new understanding of the impact clinical errors have on medical imaging technologists. Furthermore, this research has several implications for future research and practice in New Zealand and internationally and provides an opportunity for expanding this research to a wider population.